Energy Sources and Thermal Management Technologies for Electric Vehicle Batteries: A Technical Review - Md Atiqur Rahman; Gurrala Mohith Venu Reddy; Rajeshwari Chatterjee; Soumili Hait; S. M. Mozammil Hasnain; Prabhu Paramasivam; Leliso Hobicho Dabelo (Global Challenges, 2025)
Abstract Efficient thermal management of high‐power lithium‐ion batteries (LiBs) is critical for ensuring safety, longevity, and performance in electric vehicles (EVs). Battery thermal management systems (BTMS) play a crucial role in regulating temperature, as LiBs are highly sensitive to thermal fluctuations. Excessive heat generation during charging and discharging can degrade battery performance, reduce lifespan, and pose safety risks. Traditional cooling methods, such as air and liquid cooling, often require additional power and complex components, making them less effective for high‐energy–density batteries. As a result, recent advancements focus on immersion, indirect, and hybrid cooling solutions. Among these, phase change material (PCM)‐based BTMS has emerged as a promising passive cooling approach. PCMs efficiently absorb and store heat, maintaining optimal battery temperature without external power. Their thermal performance is further enhanced by integrating expanded graphite (EG) fillers, metal foams, or fins, improving heat dissipation. This review examines recent progress (2019–2024) in BTMS technologies, with a particular focus on PCM applications in fast‐charging conditions. It also discusses BTMS performance under extreme environments, such as high temperatures, sub‐zero conditions, and abuse scenarios. Future research directions are highlighted to optimize BTMS for next‐generation EVs, ensuring improved battery safety, efficiency, and thermal stability.